Antibacterial Activity of Alkaloids, Phenols Extracts, and Phytochemical Screening of Bioactive Compounds of Borago officinalis plant - Ekhlass Mashhad Solaq; Roaa M. H. Shoker (University of Thi-Qar Journal of agricultural research, 2025)
The overprescription and uses the antibiotics which are produced to rise of drug-resistant bacteria, and this causes a significant global public health threat, this led to discovery phytochemicals compounds such as natural products of medicinal plants which have antimicrobial agent. This study was aimed to evaluate antibacterial activity of alkaloids and phenols extracts of Borago officinalis against urinary tract infection UTI in waist province, Grampositive bacteria such as Staphylococcus aureus and Gram-negative bacteria such as Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Phenol extracts were having significant highest antibacterial activity at p≤0.05 against bacteria than alkaloids. The results showed the B. officinalis contains gallic, rutin, alkaloid, glycoside, tannins, and saponins through the estimation of active compounds in plant, The results of High-performance liquid chromatography (HPLC) showed occurrence Gallic acid, Apigenin, Ferulic acid, Qurcetine, Rutin, Sinapic acid compounds, the higher concentration compound was gallic (93.6mg/gm), while, Ferulic acid (44.6 mg/gm) lower concentration in plant. The results showed S. aureus was more sensitive for B. officinalis extracts, while P. aeruginosa was more resistance for each extract.